Synergistic Effects of Crop Aboveground Growth and Root Traits Guarantee Stable Yield of Strip Relay Intercropping Maize - Liang Feng; Yun Hu; Kai Shi; Haiying Tang; Tian Pu; Xiaochun Wang; Wenyu Yang (Agronomy, 2024)
In order to reveal the yield-increasing mechanism of relay intercropping (RI) maize with different varieties from the perspective of plant growth, source sink relationship, and root growth, a two-factor randomized block design trial was designed, which includes different maize varieties (Rongyu1210 (RY1210), Zhongyu 3 (ZY3)) and plant pattern (RI, Sole cropping (SC)). The leaf area index (LAI), dry matter accumulation and distribution, root dry weight (RDW), root length (RL), root surface area (RSA), root volume (RV), and maize yield were determined. LAI of RI RY1210 was significantly higher than that of the SC RY1210 at the filling stage and maturity stage. The dry matter accumulation of RI RY1210 ear was significantly higher than that of SC RY1210 and RI ZY3, and the RDW of RY1210 was significantly higher than that of ZY3. The ratio of RDW of RI RY1210 was higher than that of RI ZY3 in the 20–40 and 40–60 cm soil layers, respectively. The RDW, RL, RV, and RSA of RI RY1210 were significantly lower than that of sole RY1210 by 25.43%, 10.75%, 30.79%, and 23.73%, respectively, but higher than that of RI ZY3 by 143.98%, 278.29%, 54.40%, and 29.57%, respectively. The average yield of RI RY1210 was 8782.71 kg ha−1, with no significant difference compared to SC, which was mainly attributed to a larger ear dry matter accumulation, higher LAI in later growth stages, larger RDW, and the ratio of roots in deeper soil layers. This study will be useful and helpful to farmers for how to select and plant high-yielding maize varieties in strip relay intercropping.